KARAKTERISTIK MORTAR POLIMER DENGAN BINDER AKRILIK PADA AIR NORMAL DAN KONDISI NORMAL - Rianti Ratna Dewi; Ismeddiyanto; Edy Saputra (Jurnal Teknologi dan Rekayasa Sipil, 2024)
Mortar is an important binding matrix in construction, playing a role in protecting structures from damage and cracking. Handling seepage and corrosion in structures is a major concern. Research shows that the addition of Acrylic Binder to mortar mixes improves weathering, chemical, abrasion resistance and adhesive strength. This study aims to assess the characteristics of mechanical and physical properties of mortar with the addition of acrylic binder in polymer mortar. The results of the study with the addition of acrylic binder through treatment in normal water and normal conditions with a variation of 3 substitutions namely 40%, 30%, 20% and 0% which is needed as a control, showed an increase in the highest compressive strength value in the addition of 30% acrylic binder with the strength obtained of 26 Mpa at the age of 28 days. The lowest water absorption was 4.35% at 28 days, with a porosity of 9.3% and surface absorption of 0.14. These results show that the addition of acrylic binder increases the water tightness of the mortar, demonstrating the potential application of this polymer mortar in improving structural performance.